1979
DOI: 10.2307/1942471
|View full text |Cite
|
Sign up to set email alerts
|

Late Quaternary Vegetation of Central Appalachia and the New Jersey Coastal Plain

Abstract: Pollen and plant macrofossil studies at 11 sites in New Jersey, southern and eastern Pennsylvania, West Virginia, and Virginia, USA reveal the character of the stable vegetation of the unglaciated eastern United States while the Wisconsin ice sheet was still at its outer limit. Grass—dominated tundra with dwarf shrubs was present 60 km south of the ice front at Longswamp, Pennsylvania. Sedge tundra covered the higher mountains of central Appalachia. In southern Pennsylvania, New Jersey (including the Pine Barr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

12
182
1

Year Published

1989
1989
2015
2015

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 254 publications
(195 citation statements)
references
References 69 publications
(81 reference statements)
12
182
1
Order By: Relevance
“…indicates that the rock block slide and subsequent formation of a small sedimentary basin behind it occurred prior to Holocene time. This date does not correspond well with the pollen age obtained by comparison of the pollen profile at this site to the pollen profiles at Delcourt and Delcourt's (1986) dated Saltville site (middle to late Holocene), but does correlate well with the Potts Mountain Pond site (Watts, 1979). The assumption is thus made that local site differences may indeed mask regional vegetation patterns.…”
contrasting
confidence: 60%
See 1 more Smart Citation
“…indicates that the rock block slide and subsequent formation of a small sedimentary basin behind it occurred prior to Holocene time. This date does not correspond well with the pollen age obtained by comparison of the pollen profile at this site to the pollen profiles at Delcourt and Delcourt's (1986) dated Saltville site (middle to late Holocene), but does correlate well with the Potts Mountain Pond site (Watts, 1979). The assumption is thus made that local site differences may indeed mask regional vegetation patterns.…”
contrasting
confidence: 60%
“…The following comments are paraphrased from Thompson's report: He found that both the surface and the basal samples were similar in overall compositon but had minor differences in minor taxa and in relative proportions. Since the basal sample included a very low abundance of pine pollen and completely lacked spruce and fir pollen, an age later than earliest Holocene is suggested because fir, spruce, and pine pollen are common in regional pollen spectra of late Wisconsin and earliest Holocene age (according to Craig, 1969;Maxwell and Davis, 1972;Watts, 1979;and Delcourt and Delcourt, 1986). At the nearest previously studied site (Potts Mountain Pond, Va.), spruce and fir disappear by approximately 9,000 yrs B.P.…”
mentioning
confidence: 99%
“…Pollen evidence suggests that when the Wisconsin glaciation was at its maximum, tundra vegetation extended considerably south of the glacial margin (Maxwell & Davis, 1972;Watts, 1979Watts, , 1983, and that spruce and pine forests (indicative of a climate that crickets would tolerate) did not return to New England until 12 000-10 000 years ago. Clearly the northern field cricket populations have been established since the glaciers retreated.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, Quercus species now represent a significant proportion of northern hardwoodconifer forests, and Q rubra in particular has developed prominence (Whitney and Davis, 1986;Crow, 1988). We studied the presettlement forest records and current forest composition and structure of 46 Q rubra forests along an edaphic gradient in northcentral Wisconsin to gain an understanding of their historical development and current and future ecological status (Nowacki et al, 1990 (Crow, 1988 (Day, 1953;Watts, 1980;Lorimer, 1985;Patterson and Sassaman, 1988;Abrams, 1992 (Keever, 1953) (tables II and III). In southwestern Virginia, Q rubra represented 69% importance in forests where C dentata formerly comprised up to 85% of the canopy (Stephenson, 1986 (Braun, 1950 Interestingly, the increase in P strobus was followed by a wave of Q rubra and Q velutina recruitment, suggesting possible facilitation of these red oaks by P strobus (cf Crow, 1988;Abrams, 1992 (fig 4; Abrams, 1986).…”
Section: Maple-beech-basswoodmentioning
confidence: 99%
“…For (Horsley and Marquis, 1983;Crow, 1988;Steiner et al, 1993). It (Watts, 1980;Davis, 1985;Webb, 1988).…”
Section: Drought Adaptationsmentioning
confidence: 99%